Changes in Personal Values in Pandemic Times. Issue 2 (March 2022) - Daniel, Ella; Bardi, Anat; Fischer, Ronald; Benish-Weisman, Maya; Lee, Julie A.
The COVID-19 pandemic has had immense impact on people's lives, potentially leading individuals to reevaluate what they prioritize in life (i.e., their values). We report longitudinal data from Australians 3 years prior to the pandemic, at pandemic onset (April 2020, N = 2, 321), and in November–December 2020 ( n = 1, 442). While all higher order values were stable prior to the pandemic, conservation values, emphasizing order and stability, became more important during the pandemic. In contrast, openness to change values, emphasizing self-direction and stimulation, showed a decrease during the pandemic, which was reversed in late 2020. Self-transcendence values, emphasizing care for close others, society, and nature, decreased by late 2020. These changes were amplified among individuals worrying about the pandemic. The results support psychological theory of values as usually stable, but also an adaptive system that responds to significant changes in environmental conditions. They also test a new mechanism for value change, worry.